An Analysis upon Present Trends and Practices of Intellectual Property Rights in India: Exploring the Changing Landscape of Intellectual Property Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Global aggressiveness has re-imagined business procedures worldwide and the concentration has absolutely moved to looking at how our knowledge assets can reposition our remain in the world market. It implies that procedure of riches creation is changing from asset based to knowledge based i.e. it now relies upon intellectual prowess and our capacity to make, to offer, to disclose and to take care of issues. Subsequently, in future the riches would increasingly leave our brains and less and less will it leave the ground. What's more, the products and ventures being made by our intellectual prowess would be marketed in the global village. Presently a fundamental issue to be tended to is that in what manner would this be able to property of knowledge be protected? What's more, before this we have to believe that how the knowledge can be changed over into property? Since knowledge is conceptual and isn't care for an auto or a house which can be bolted and secured against burglary. On the off chance that anybody picks up knowledge it doesn't diminish that accessible to others. There are two methods for transforming knowledge into property. One way is mystery, which is utilized to secure three sorts of data, to be specific trade secrets, know – how and customs. Another way is Intellectual Property Laws, including Copyright, Patent, Registered Industrial Design and Trademark, legislation and traditions.